57 Inability to Report Platelet Counts Due to Interference of Automated Platelet Counting by Microschistocytes: A Caveat in Severely Ill Patients. (11th January 2018) - Reveles, Candace; Pryor, Julie; Spier, Catherine
Abstract: Introduction: Automated hematology analyzers allow for rapid, high-throughput analyses that help guide clinical decision-making. Complete blood count results generated are reliable, but have limitations. When utilizing the Beckman Coulter Unicel DxH 800 Coulter Cellular Analysis System (Beckman Coulter Diagnostics, Brea CA), interference of red blood cell fragments with the platelet count is recognized. Since red blood cell fragmentation may occur in critically ill patients who also require platelet counts, how to effectively mitigate such results is crucial. Methods: Review of complete blood count results and blood smears (as indicated) was performed on all patients from September 1, 2016 to January 27, 2017. Five patients were found who could not have platelet counts reported due to the presence of numerous microschistocytes that interfered with the automated platelet count. The patients ranged in age from 4 days to 69 years; diagnoses included abdominal pain, congenital heart disease, prematurity complications, cardiac arrest, and treated acute myeloid leukemia. The platelet count was not reported when the manual estimate and automated counts were discrepant by >20%. Three patients are alive and two have died. The interference of the platelet count by microschistocytes was noted in all patients and resolved in those that survived. Conclusion: Microschistocytes occur in many different disease states and may cause spuriously high platelet counts. This interference may cause a serious delay in the reporting of automated platelet counts, or may preclude platelet enumeration entirely. It is essential that the laboratory recognizes this interference and has a clearly defined policy for reporting platelets when schistocytes, especially microschistocytes, are present. Close communication with the clinical team, especially when the microschistocytes are no longer an interference, is required for optimal patient care.